Nodes of knowledge, managing transfer: Shipbuilding and repair during the transformation from sail to steam. (March 2023) - Brandon, Pepijn; Dondorp, Marten
The core theme of the special issue in which this article appears is the inherent impossibility of confining the knowledge required to build and sustain the instruments of travel to a single space or institution. This is certainly true for the ships that built empires – the large sailing and later steam ships produced by navies and companies in the process of European expansion. Ships traveled between polities and required repairs overseas, taking the construction knowledge and practices with them. Skilled laborers – experienced shipwrights and increasingly also trained engineers – helped to transfer shipbuilding practices across oceans, and to adapt these practices to local conditions based on forms of "blended know-how." This article explores how the circulation of shipbuilding knowledge and practices within and between maritime empires changed with the increasing pace of industrialization. It does so on the basis of three moments: the Dutch East India Company's shipbuilding activities in Asia in the seventeenth and eighteenth centuries; the interaction between private industry and the Dutch state in advancing machine-manufacturing in both the Netherlands and on Java in the 1830s and 1840s; and the aid provided by Dutch engineers in laying the groundwork for Japanese industrial warship-construction in the second half of the nineteenth century. Such transfers put high demands on the capacities of states and naval administrators in controlling the flows of necessary resources and skilled labor, requiring complex arrangements between states and private capital. Industrialization did not change this basic fact, but it did change the nature of these arrangements. Although shipbuilding knowledge always remained practice-driven, highly mobile and susceptible to local adaptation, the increasing technological demands created by the transition from sail to steam and wood to iron, combined with the extension of the power of states and transnationally operating manufacturing companies, considerably changed the institutional embeddings and societal consequences of its circulation.